2022
DOI: 10.1364/oe.478688
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative investigation on a period variation reduction method for the fabrication of large-area gratings using two-spherical-beam laser interference lithography

Abstract: Gratings produced by two-spherical-beam Laser Interference Lithography (LIL) will have a nonuniform period, and the associated period variation is larger with the increase of the substrate size. This work quantitatively investigates a noninvasive method for improving the period variation on 4-inch silicon wafers. By temporarily deforming the flexible silicon wafer using a customized concave vacuum chuck [J. Vac. Sci. Technol. B 19(6), 2347 (2001)10.1116/1.1421558], we show that the fabricated gratings will hav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The first step was the fabrication of a master sample by interferential photolithography 28 with a period Λ = 630 nm and a depth d = 80 nm. The AFM profile of this sample is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The first step was the fabrication of a master sample by interferential photolithography 28 with a period Λ = 630 nm and a depth d = 80 nm. The AFM profile of this sample is shown in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Unlike finesse in engraving, these methods are not efficient due to the type of serialization [27]. A more suitable fabrication method is laser-assisted lithography, which includes nanoimprint lithography [28] and laser interference lithography (LIL) [29]. By these methods, sub-100 nm structures have been fabricated.…”
Section: Design and Methodologymentioning
confidence: 99%
“…LIL also enables fabrication of nanograting on large areas. In addition, another study [153] experimentally showed that this effect can be significantly reduced (by 86%) for such gratings by adding a simple a concave vacuum chuck to the traditional setup used for LIL. Yet, we observed that a prolonged exposure to fluids of the gratings produced by LIL was damageable and modified the surface of these samples.…”
Section: Fabrication Of the Grating Couplersmentioning
confidence: 99%